Conversational Implicature, Grice's Theory of Conversation: A Pragmatic Analysis of Some Qur'anic Narratives - Haifa Mohammad Nassar; Moustafa Ali Al-Hamzi (Hasanuddin University, 2025)
Though Grice's theory of implicature has been discussed in spoken and written interactions in various languages, studies that examine this theory in the Qur'anic Arabic language have been scarcely conducted. The aim of this paper is to present the flouting of Grice's maxims of conversation in the Holy Qur'an to generate implicatures, identify their types, and understand their functions. A descriptive qualitative method was used. Based on eight selected Qur'anic stories, ten particularized conversational implicatures were found in the Arabic text of the Qur'an which performed various functions. They were triggered via flouting the conversational maxims of Quality, Quantity, Manner, and Relevance. It is also worth noting that the maxims of Quality and Quantity were much more flouted than the Manner and Relevance maxims. As aspects of Arabic Language in the Qur'anic texts are required to be studied in their pragmatic mechanisms, this study may help to provide understanding of implicatures in the Holy Qur'an. This study also gives contribution to the field of pragmatics especially in implicature conception or other rhetorical studies that pertain to the Holy Qur'an.